Intensidade da podridão-da-haste em mamoeiro causada por isolados de Lasiodiplodia theobromae com diferentes níveis de sensibilidade a fungicidas. - GONÇALVES, Amanda de Melo (2011)
Papaya is a fruit tree common in almost all countries of Tropical America. Its products are used for different uses in textile, pharmaceuticals, food and cosmetics industries. The Brazil is the world's leading producer and most of its production is for export. Several diseases affect the crop and are its main limiting factor, causing major damage to production and marketing. The main losses are responsible for diseases post-harvest, which occur during storage of the product, however, the rot in the middle part of the stem, caused by Lasiodiplodia theobromae, has been highlighting the culture. The disease spreads rapidly and has been observed decimating an entire orchard papaya, the symptoms are initially soaked lesions, showing disintegration of tissues and formation of pits, which under predisposing conditions evolve, surrounding the stem, causing it to overturn. There is little information regarding the development of the disease and prevention is the best control measure. Chemical control is already used when the disease is detected, but there is no product registered for pathosystem in this field. The lack of knowledge of the interaction pathogen-host added to the misuse of these continuous products can result in failure of control. Studies sensitivity to fungicide isolates found not sensitive to these products, which can complicate treatment and control of disease, demonstrating the importance of studying the behavior of these isolates in plants.